2015
DOI: 10.1037/pst0000015
|View full text |Cite
|
Sign up to set email alerts
|

The role of deliberate practice in the development of highly effective psychotherapists.

Abstract: Little empirical research exists about highly effective psychotherapists, and none about the factors that mediate the acquisition and maintenance of superior performance skills (e.g., Ericsson, 1996, 2006; Ericsson, Krampe, & Tesch-Romer, 1993). In the full sample, a 3-level multilevel modeling (Level 1: clients; Level 2: therapists; Level 3: organization types) of practitioner outcomes was used to examine the contribution of the therapist to treatment effectiveness. Consistent with prior research, in the full… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
224
0
19

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 230 publications
(254 citation statements)
references
References 54 publications
11
224
0
19
Order By: Relevance
“…These findings combined with the literature which demonstrates that psychotherapist effectiveness can be improved even after registration -through avenues such as routine outcome monitoring, seeking feedback from clients, purposeful practice and a focus on the working alliance (e.g. Chow et al, 2015;Miller et al, 2013;Lambert, 2017) -highlights the need for ongoing training of clinicians and controlling for these factors when examining psychotherapist outcomes in non-training environments. Todd et al (1994) recommended that to advance the literature, several methods should be employed: expanding beyond one specific research topic; including contextual information about the clinic and training practices; describing how participant samples compare to the population the clinic serves; comparing what differentiates training clinic environments from each other, such as by differences in service or training, and how these differences might relate to clinical outcomes; encouraging collaboration between training clinics and pooling data across settings;…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…These findings combined with the literature which demonstrates that psychotherapist effectiveness can be improved even after registration -through avenues such as routine outcome monitoring, seeking feedback from clients, purposeful practice and a focus on the working alliance (e.g. Chow et al, 2015;Miller et al, 2013;Lambert, 2017) -highlights the need for ongoing training of clinicians and controlling for these factors when examining psychotherapist outcomes in non-training environments. Todd et al (1994) recommended that to advance the literature, several methods should be employed: expanding beyond one specific research topic; including contextual information about the clinic and training practices; describing how participant samples compare to the population the clinic serves; comparing what differentiates training clinic environments from each other, such as by differences in service or training, and how these differences might relate to clinical outcomes; encouraging collaboration between training clinics and pooling data across settings;…”
Section: Discussionmentioning
confidence: 80%
“…If this integration occurs from the outset of training, it may be more likely to be integrated after completion of training as barriers to practitioners integrating research may be due to a lack of training, or to not seeing the relevance to their practice (Neufeldt & Nelson, 1998). However, research is finding that the most effective psychotherapists are those who engage in deliberate practice (Chow et al, 2015), integrating feedback and routine evaluation of outcomes into their practice (Miller et al, 2013): skills which can be developed through training in research and evidence-based care. Thus, if the eventual goal of training is to make the most effective psychotherapists who can alleviate distress for their clients, bringing research into training clinics may be seen as an integral part of training.…”
Section: Implications and Practical Significance Of This Reviewmentioning
confidence: 99%
“…The finding in the current study that therapist clinical experience was found to be negatively associated with outcome could possibly be a result of therapists with high clinical experience exhibiting a different behavioural profile than do less experienced therapists (e.g., being less adherent to the treatment protocol or less involved in maintaining therapeutic skills associated with patient outcomes). A recent study investigating characteristics of highly effective psychotherapists found that the amount of time spent on improving therapeutic skills (i.e., deliberate practice) predicted positive client outcomes (Chow et al, ). A case study focusing on an agency that implemented deliberate practice and routine outcome monitoring also indicated that therapists improved their outcomes over time (Goldberg et al, ), in contrast to other studies (e.g., Goldberg, Babins‐Wagner, et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Deliberate practice, defined as "individualized training activities especially designed… to improve specific aspects of an individual's performance through repetition and successive refinement" (Ericsson & Lehman, 1996), is an important mechanism for increasing expertise in psychotherapy (Goodyear, Wampold, Tracey, & Lichtenberg, 2017). Therapists who engage in more frequent deliberate practice to improve their therapeutic skills have shown better client outcomes (Chow et al, 2015). It may be difficult to imagine how focused, deliberate practice could apply to psychotherapy, which is complex, dynamic, and allows for substantial latitude in focus and prioritization, even in manualized treatments.…”
Section: Deliberate Practicementioning
confidence: 99%